2014
DOI: 10.1186/2049-3258-72-14
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated literacy level does not explain educational differences in health and disease

Abstract: BackgroundAlthough literacy is increasingly considered to play a role in socioeconomic inequalities in health, its contribution to the explanation of educational differences in health has remained unexplored. The aim of this study was to investigate the contribution of self-rated literacy to educational differences in health.MethodsData was collected from the Healthy Foundation and Lifestyle Segmentation Dataset (n = 4257). Self-rated literacy was estimated by individuals’ self-reported confidence in reading w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…Our results support findings that specific population subgroups are vulnerable to perpetuating poor health due to low health literacy. 8,9,22,43,[46][47][48][49][50][51] In parallel with other studies utilizing the HLQ as a measurement tool, our findings highlight that those with low health literacy were more likely to earn a lower income, be unemployed, have comorbidities, have lower education, have a mental health condition, or live alone. 43,46 Low health literacy is consistently associated with poorer diabetes knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Our results support findings that specific population subgroups are vulnerable to perpetuating poor health due to low health literacy. 8,9,22,43,[46][47][48][49][50][51] In parallel with other studies utilizing the HLQ as a measurement tool, our findings highlight that those with low health literacy were more likely to earn a lower income, be unemployed, have comorbidities, have lower education, have a mental health condition, or live alone. 43,46 Low health literacy is consistently associated with poorer diabetes knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Other types of health literacy may be more relevant for Asian American cancer screening (Baker 2006 ). Furthermore, while previous studies have found self-reported literacy and health literacy to be stronger explanatory factors for some health disparities than race/ethnicity (Sentell and Halpin 2006 ; Bennett et al 2009 ; Howard et al 2006 ), this relationship is not consistent across all outcomes, suggesting that literacy and health literacy may work distinctly in different health areas (Bennett et al 2009 ; Fransen et al 2014 ). Also, the CHIS only included a health literacy measures in the 2007 data.…”
Section: Discussionmentioning
confidence: 88%
“…Low socio-economic status in terms of lower income, lower educational attainment and lower literacy levels [36, 37] are associated with poor health outcomes [38]. Likewise, inadequate health literacy is associated with lower knowledge or disease etiology and prevention [39, 40]. Overall, non-Hispanic black women have a lower socio-economic status when compared to non-Hispanic white women.…”
Section: Discussionmentioning
confidence: 99%